Legal Expertise on Corporate Audit Committees and Financial Reporting Quality - Krishnan, Jayanthi; Wen, Yuan; Zhao, Wanli (The Accounting Review, 2011)
ABSTRACT Recent trends in corporate board composition indicate an increase in the appointment of directors with legal expertise. Using two financial reporting quality measures, accruals quality and discretionary accruals, we find—for a sample of Russell 1000 firms in 2003 and 2005—that the presence (and proportion) of directors with legal backgrounds on the audit committee is associated with higher financial reporting quality. These results obtain after controlling for accounting expertise on audit committees. Also, supplementary tests indicate a positive association between changes in legal expertise and changes in financial reporting quality, suggesting that legal expertise serves as a monitor rather than as a signal of financial reporting quality. Further, the two forms of expertise interact —i.e., the presence of directors with both forms of expertise enhances financial reporting quality, beyond the contribution of the individual forms of expertise. Additional tests suggest that the positive effects of legal expertise are greater in the post-SOX period compared with a pre-SOX year.